Pelaksanaan Perlindungan Hukum Usaha Mikro Kecil dan Menengah Berbasis Perjanjian Kemitraan untuk Meningkatkan Daya Saing dalam Era Ekonomi Global (Studi di Sentra Industri Keripik Tempe dan Keramik Dinoyo): Implementation of Legal Protection for Micro, Small and Medium Enterprises Based on Partnership Agreements to Increase Competitiveness in the Global Economic Era (Study at the Dinoyo Tempe Chips and Ceramics Industrial Center) - Sukarmi; Ganindha, Ranitya; Umar, Azahlia (Warkat, 2021)
MSMEs have an important step in supporting the improvement of the Indonesian people's economy, especially in terms of business opportunities and employment opportunities. Malang City is famous for its tourism and education sectors where MSMEs are an inseparable part of the economic activities of the Malang community. Malang City has several MSME industrial centers. This research examines the form of partnership agreement between the sanan tempeh chips and dinoyo ceramics industry center with large business partners in Malang City and hotels in Malang City. Researchers analyze the implementation of legal protection in partnership agreements in Malang City and analyze the fulfillment of the principles of fair partnership agreements. For this reason, in this paper the problem that will be studied is: How is the analysis of partnership agreements between MSMEs and large businesses in Malang City, and how is legal protection implemented for Partnership-based MSMEs in Malang City? This article is based on empirical juridical research with a Sociological Juridical approach which produces an analysis that: The implementation of the Partnership agreement in Malang City has not been carried out effectively which is contrary to the rules in Government Regulation Number 17 of 2013 where the concept, form of agreement and terms of partnership are not partnerships as stated in which has been mandated by law. A true partnership must be accompanied by a program of empowerment and assistance for large business actors towards small business actors. Meanwhile, large business actors themselves have a tendency not to carry out partnerships as they should. Implementation of legal protection and implementation of supervision over partnership agreements in Malang City is also still not running effectively due to overlapping authority.